Droplet evaporation and boiling for different mixing ratios of the silver-graphene hybrid nanofluid over heated surfaces. (December 2021) - Siddiqui, F.R.; Tso, C.Y.; Fu, S.C.; Qiu, H.H.; Chao, Christopher Y.H.
Highlights: The MR-2 SGHF exhibits the highest synergistic thermal conductivity. The low mixing ratio droplets give highest evaporation rates for 25 °C≤ Ts ≤ 100 °C. The high mixing ratio droplets give highest evaporation rates for 103 °C≤ Ts ≤ 125 °C. The SGHF droplet evaporation rate on residue is up to 10 times that on copper. The latent heat flux removal up to 890 W/cm 2 is obtained using SGHF droplets. Abstract: Thermal management of many high heat flux devices depends on droplet based cooling, such as the spray cooling or electro-wetting for hotspot cooling. Recently, heat dissipation in these devices increased to unprecedented levels, pressing a need for advanced thermal fluids in droplet based cooling systems. In this paper, we address this challenge by investigating the evaporation and boiling performance of the silver-graphene hybrid nanofluid (SGHF) droplet for its various mixing ratios and droplet sizes on a heated copper and a residue surface, obtained from the evaporation of the first SGHF droplet. The results show that low mixing ratio (MR ≤ 0.1) SGHF droplets exhibit highest evaporation rates for substrate temperature ( Ts ) in a range of 25 °C ≤ Ts ≤ 100 °C. However, this trend is reversed in the nucleate boiling regime, where high mixing ratio (MR ≥ 0.9) droplets give highest evaporation rates. Moreover, all SGHF droplets, irrespective of their mixing ratio, exhibit similar evaporation rates in the film-boiling regime. Furthermore, the SGHF droplet evaporation rate on its porous residue surface increases up to 173% for 25 °C ≤ Ts ≤ 100 °C and by an order of magnitude in the nucleate boiling regime as compared to a plain copper surface. We also show that besides the synergistic thermal effect, the thermal Marangoni convection also affects the SGHF droplet evaporation rate. Moreover, we develop a diffusion-convection evaporation model that can predict the evaporation rate for different mixing ratios of the SGHF droplet on heated copper and residue surfaces. Moreover, we demonstrate that the latent heat flux up to 890 W/cm 2 and 850 W/cm 2 can be achieved using a SGHF droplet on heated copper and residue surfaces, respectively, suggesting its potential application in high heat flux device cooling. Finally, we discuss the effects of spray hydrodynamic parameters on critical heat flux of the SGHF spray cooling.